Difference in Cortical Relay Time Between Intrinsic Muscles of Dominant and Nondominant Hands. Issue 4 (4th July 2017) - Kirimoto, Hikari; Tamaki, Hiroyuki; Onishi, Hideaki
ABSTRACT: The authors aimed to calculate and compare cortical relay time (CRT) between intrinsic hand muscles and between homonymous muscles of dominant and nondominant hands. The participants comprised 22 healthy volunteers. The CRT for long-latency reflexes (LLRs) was calculated by subtracting the peak latency of somatosensory evoked potentials of component N20 and the onset latency of motor evoked potentials from the onset latency of LLRs. CRT was significantly shorter for the first dorsal interosseous muscle than for the abductor pollicis brevis muscle, regardless of hand dominance. CRT for the abductor pollicis brevis muscle was significantly shorter in the dominant hand than in the nondominant hand. Evaluation of CRT for intrinsic muscles might be beneficial in the understanding of individuated finger functions.